Penerapan Teknologi Location Base Service (LBS) dalam Pencarian Stok Ketersedian Gas Bersubsidi di Distributor Resmi - Ardi Wijaya; Rozali Toyib; M Sapta Pirdaus; Della Rahma Della (UNIVED Press, 2025)
The main problem is the distribution of these gases. Many other areas experience gas shortages, especially before holidays or other big events, it is difficult to obtain gas at such times. after conducting further investigation, I discovered that there were a number of games taking place in certain locations, most agents held back gas sales and waited for shortages so that gas prices could increase significantly and this also happened due to high public demand for gas at certain times, such as during Eid al-Fitr which has just passed, and this situation can arise when public demand increases, so that gas stocks can quickly decrease, without being balanced by equal distribution of gas. The solution to this problem is to develop an Android application that can show the location of places that provide gas, as well as monitoring gas stocks available in several locations. It is hoped that this can reduce gas containment measures, because this application can track who has purchased gas and who has not. In conclusion, this system makes it easy for users to obtain reel time information, but there are weaknesses that are influenced by the presence of open and closed spaces and inaccuracies between actual locations.